Stereotactic body radiation therapy for adrenal gland metastases: A multi-institutional outcome analysis - C. Yuste; V. Passerat; G. Calais; B. Schipman; L. Vaugier; A. Paumier; A. Huertas; CG. Hemery; C. Debelleix; J. Chamois; N. Blanchard; AL. Septans; et al. (Clinical and Translational Radiation Oncology, 2024)
Aim: The adrenal gland is a common site of metastasis with a rate of up to 27% in autopsy series. The incidence of these metastases is increasing due to greater use of Positron Emission Tomography scans and improved overall survival of patients with metastatic cancers. Stereotactic body radiation therapy (SBRT) is a non-invasive treatment option for metastasis. The aim of this study is to assess prognostic factors influencing local control, progression-free and overall survival in oligometastatic patients treated with SBRT for an adrenal metastasis. Methods: In this multicentric retrospective study, we included patients with adrenal metastases treated with SBRT between 2010 and 2021 in eleven french centers. All primary tumors were included. Results: A total of 110 patients treated for 121 adrenal lesions were included. Non-small-cell lung cancer was the predominant histologic type (55.4 %). Eighty-two percent of patients had at least 2 metastatic sites. The median Planning Target Volume was 70 cm3 with a median prescription dose of 40 Gray (Gy). The mean Biologically Effective Dose (BED) 10 dose was 74.2 Gy. Local control at 1 and 2 years was 85.9 % and 72.5 % respectively. The median overall survival and progression-free survival were 31.6 and 8.5 months respectively. Local control was significantly improved by systemic treatment one month before or after SBRT (p = 0.009) and by a BED10 greater than or equal to 50 Gy (p = 0.003).In multivariate analysis, oligometastatic presentation (p = 0.009) and a metachronous metastatic presentation (p = 0.008) were independent factors for progression-free survival.Tolerance was excellent, no grade 3 and 4 toxicities were described due to SBRT. Conclusion: Stereotactic radiotherapy of adrenal metastases makes possible a local control of more than 85% at one year and was well tolerated. The factors influencing survival in oligometastatic patients still need to be found in order to better select those who benefit the most from this type of treatment.